PENINGKATAN DAYA SAING UMKM DI MARKETPLACE MELALUI PEMANFAATAN KONTEN VIDEO DAN PEMBERDAYAAN SDM DI CIKARANG SELATAN - Setiadi , Iwan Kresna; Warsidi, Warsidi; Kresna , Abdul Aji; Supriadi , Yudi Nur (Gapenas Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, including in the Cikarang Selatan region. However, many MSME actors still face challenges in digital marketing, particularly in utilizing video content as a promotional tool on online marketplaces. According to data from the Ministry of Cooperatives and SMEs, MSMEs contribute up to 60.5% of Indonesia’s GDP, emphasizing their position as the backbone of the national economy. Meanwhile, a study by Wyzowl shows that 86% of marketers use video as a marketing tool, and 92% consider it effective, highlighting the urgency to enhance MSMEs’ digital capabilities. MSMEs in Cikarang Selatan often lack the skills to produce engaging video content, develop compelling promotional scripts, understand marketplace algorithms, and edit videos professionally. These limitations result in low product exposure and weakened competitiveness in the digital ecosystem. This community engagement program aims to strengthen MSMEs’ abilities in producing and marketing video content through several interventions: video marketing training, hands-on workshops on video production using smartphones, video editing training using user-friendly applications such as CapCut and Canva, marketplace optimization strategies, as well as evaluation and promotional simulations. The program will be implemented over seven months using interactive training, practical sessions, and mentoring by digital marketing practitioners and professional videographers. Expected outputs include improved digital skills among MSME participants, production and upload of at least 10 promotional videos, development of a training module, and increased engagement and sales potential for participating MSMEs. Through this program, MSMEs in Cikarang Selatan are expected to optimize the use of video content, enhance competitiveness, and expand market reach in the digital era.